Aboveground biomass estimation and carbon stock assessment of mahogany (Swietenia macrohylla king) and yemane (Gmelina arborea Roxb.) in Angat watershed reservation - Barrias,Carolyn D.; Moya, tolentino B. (Quezon City Institute of Environmental Science and Meteorology, College of Science, University of the Philippines Diliman, 2010)
In this study, the ngat watershed reservation reforestation project have roughly sequestered between 1,018.62 and 1,682.68 ton CO2/hectare as estimated correspondingly by the Tandug (2006) and Brown (1997) allometric equation. Most of the total carbon (about 80%), has been sequestered by 25-year old mahogany and Yemane trees; the rest by the 5-year old trees. Regardless of the allometric equations used, Mahogany produced higher total aboveground biomass and therefore stored higher carbon than Yemane at both age groups.
Thesis (M.S.-Environmental Science)--University of the Philippines Diliman
Keywords: Watershed management -- Philippines